Beginning OpenOffice 3 - Channelle, Andy (Apress, 2012)
Office suites are one of the most popular types of software, and most computer users will, at some point, find themselves staring at the user interface of a word processor, spreadsheet, or presentation package. Traditionally, office suites have been quite expensive packages, but thanks to the generosity of Sun Microsystems and a massive community of developers, writers, and testers, there is an alternative to shelling out hundreds of dollars or taking the risks (computer viruses, law suits) associated with downloading and running pirated editions of commercial software. OpenOffice.org (which is both product name and web address) is a piece of software that offers access to the most common features used in office environments, and some of the more uncommon ones too. In addition to being a great collection of applications, one of the revolutionary things about this “business class” software is that it costs less than your daily paper. In fact, anyone—individuals, businesses, charities, governments—can download and install OpenOffice.org for absolutely nothing. And this isn’t trial software; it’s not restricted in any way. Who said there’s no such thing as a free lunch?